2020
DOI: 10.3390/polym12040837
|View full text |Cite
|
Sign up to set email alerts
|

Using 3-Isocyanatopropyltrimethoxysilane to Decorate Graphene Oxide with Nano-Titanium Dioxide for Enhancing the Anti-Corrosion Properties of Epoxy Coating

Abstract: In this paper, the graphene oxide loaded with nano titanium dioxide (TiO2–GO) was synthesized through 3-isocyanatopropyltrimethoxysilane (IPTMS) and characterized by Fourier transform infrared spectroscopy (FTIR), X-ray diffraction analysis (XRD), X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM), thermogravimetric analysis (TGA), and dispersion test. The results illustrated our modification was successful and TiO2–GO was transferred from hydrophilic to hydrophobic. That greatly enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…It has been demonstrated that PMMA-based BCs cannot form covalent bonds with the natural bone, and a lack of interactions may induce implant loosening after a while. According to the results, the addition of CNTs, GO, and carbon-based composites [ 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 ] can enhance the setting times, temperature, strength, bioactivity, and cellular activity of the PMMA-based BCs. However, it is believed that utilization of GO could have further impact than CNTs reinforcing agents on enhancement of the strength and durability of PMMA-based BCs, conquering the potential issue presented by premature failure of the implant.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that PMMA-based BCs cannot form covalent bonds with the natural bone, and a lack of interactions may induce implant loosening after a while. According to the results, the addition of CNTs, GO, and carbon-based composites [ 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 ] can enhance the setting times, temperature, strength, bioactivity, and cellular activity of the PMMA-based BCs. However, it is believed that utilization of GO could have further impact than CNTs reinforcing agents on enhancement of the strength and durability of PMMA-based BCs, conquering the potential issue presented by premature failure of the implant.…”
Section: Discussionmentioning
confidence: 99%
“…Since epoxy resins have good adhesion to most materials [ 28 , 29 , 30 ], we used the developed compositions for the fire protection of wood. Wood samples with a fire-resistant coating (100 ED-20 + 40 ORFF + 50 Diorite + 15 PEPA) were obtained.…”
Section: Resultsmentioning
confidence: 99%
“…Varying chemical procedures are utilized in combining polymeric matrices with nanoparticles. These procedures include melt and solution intercalation, in situ and emulsion polymerization [36] , [37] , [38] , [39] . Relative to dispersion and distribution of nanoparticles’ in PNCs, both solution intercalation and situ polymerisation are perceived excellent for PNCs fabrication.…”
Section: Pnc Coatings Properties and Classificationmentioning
confidence: 99%